Development of a Spatial Geometry Instrument Based on Minimum Competency Assessment - Ariyanto, Lilik; Kusumaningsih, Widya; ., Supandi (KnE Social Sciences, 2024)
This research aims to develop a spatial geometry instrument based on minimum competency assessment. Spatial geometry is a field of mathematics that is important in developing an understanding of shape, size, and spatial relationships between objects in 3-dimensional space. Minimum competency assessment is an approach to measuring the basic understanding that individuals must have in a field of science. The research method used in this research involves the instrument development stage which consists of identifying minimum competencies in spatial geometry, designing the assessment instrument, validation by experts, and testing the instrument on a group of participants. The results of this research are a minimum competency assessment instrument in spatial geometry that can be used to measure basic understanding in this field. It is hoped that this instrument can be a useful tool in curriculum development and assessment in the field of spatial geometry, as well as assist educators in identifying students’ level of understanding of basic concepts in spatial geometry. Apart from that this research also contributes to the development of a minimum competency assessment methodology in the context of mathematics and other fields of science. Keywords: spatial geometry, minimum competency assessment, contextual